2018
DOI: 10.1177/1367493518788477
|View full text |Cite
|
Sign up to set email alerts
|

Hearing impairment detection and intervention in children from centre-based early intervention programmes

Abstract: The study aimed to describe ages at identification and initiation of early intervention (EI) services for children enrolled in centre-based EI programmes in Gauteng, as well as to describe the nature of EI services that the children received. The researchers conducted retrospective record reviews of the EI programme files. In addition, caregivers of eight children identified with hearing impairments and enrolled in centre-based EI programmes in Gauteng completed a newly constructed questionnaire. The caregiver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 20 publications
(34 reference statements)
3
23
0
Order By: Relevance
“…Owing to the dearth of research in this area, there was a lack of results in the South African context to compare with the findings of the current study. However, the delayed communication abilities demonstrated by some of the participants were expected, on account of the late identification of the hearing impairment and subsequent late commencement of EI services reported in the current study (Maluleke et al, 2018).…”
Section: Resultsmentioning
confidence: 47%
See 3 more Smart Citations
“…Owing to the dearth of research in this area, there was a lack of results in the South African context to compare with the findings of the current study. However, the delayed communication abilities demonstrated by some of the participants were expected, on account of the late identification of the hearing impairment and subsequent late commencement of EI services reported in the current study (Maluleke et al, 2018).…”
Section: Resultsmentioning
confidence: 47%
“…Because all participants were identified late, ages at initiation of EI services were also consequently delayed (Table 2) (Maluleke et al, 2018). None of the participants received newborn hearing screening services, thus participants in the current study were identified late following maternal suspicion of the hearing impairment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This prevalence is three times higher than in developed countries (Olusanya, 2012 ). The national prevalence of hearing impairment in South Africa is estimated to be four to six in every 1000 live births in the public health care sector (Maluleke, Khoza-Shangase, & Kanji, 2019 ).…”
Section: Introductionmentioning
confidence: 99%